2020
DOI: 10.1016/j.ijfoodmicro.2020.108833
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota in Chilean chilli Capsicum annuum L. used for production of Merkén

Abstract: This work aims to provide the first study on the mycobiota present in Chilean pepper Capsicum annuum L. cv. "Cacho de Cabra" throughout the early production stages. Two hundred and forty berry fruits were sampled: 1) at the ripe fruits harvest day; 2) during drying; and 3) smoking processes. A total of 192 strains, encompassing 11 genera and 44 species, were identified through analysis of β-tubulin (benA) gene and internal transcribed spacer of ribosomal DNA (ITS) region. All collection points showed samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 71 publications
(83 reference statements)
1
17
0
1
Order By: Relevance
“…The results of the nucleotide sequence analysis of multiplexed DNA bundles using the National Center for Biotechnology Information (NCBI) program and their comparison with the data available at the National Center for Biotechnology Information NCBI (21). Sequencing was performed for the selected isolates and entered into the NCBI BLAST program to find out the similarity between them and the results in the global genebank after obtaining the nucleotide sequence of the DNA package of the local isolates and comparing them with the sequences of the same region for the global and local fungal isolates registered in (NCBI BLAST) where Aspergillus flavus showed a concordance of 99.08% with the results in the genbank, Rhizopus Stolonifer showed a concordance with the genbank with a percentage of 97.74%, Penicillium oxalicum gave a match of 96.81%, Aspergillus niger had a match of 96.01%, and paecilomyces variotii had a concordance of 95.…”
Section: Dna Sequencing Analysis Resultsmentioning
confidence: 99%
“…The results of the nucleotide sequence analysis of multiplexed DNA bundles using the National Center for Biotechnology Information (NCBI) program and their comparison with the data available at the National Center for Biotechnology Information NCBI (21). Sequencing was performed for the selected isolates and entered into the NCBI BLAST program to find out the similarity between them and the results in the global genebank after obtaining the nucleotide sequence of the DNA package of the local isolates and comparing them with the sequences of the same region for the global and local fungal isolates registered in (NCBI BLAST) where Aspergillus flavus showed a concordance of 99.08% with the results in the genbank, Rhizopus Stolonifer showed a concordance with the genbank with a percentage of 97.74%, Penicillium oxalicum gave a match of 96.81%, Aspergillus niger had a match of 96.01%, and paecilomyces variotii had a concordance of 95.…”
Section: Dna Sequencing Analysis Resultsmentioning
confidence: 99%
“…Likewise for the contamination by AFs which seems to be very variable between studies carried out in the same country, despite a certain tendency which results in a greater contamination in the countries of South-East Asia, probably due to the tropical climate which characterizes these countries and to the traditional methods of drying and processing chili peppers. Indeed, according to Costa et al (2020) peppers are among the spices that are most prone to mold contamination, in particular by potentially mycotoxigenic species. The author highlights the critical factors favouring fungal development and mycotoxin synthesis all through the pepper powder production chain such as excessive irrigation and fertilizer application, late harvest, sun drying (processing time, exposure to soil insects, and spoilage fungi), conditions of transport (hygiene, humidity, and temperature control), and packaging (rehydration, packaging material).…”
Section: Discussionmentioning
confidence: 99%
“…Berry fruits of C. annuum L. cv. “Cacho de Cabra” were provided by 8 farmers as previously reported by Costa et al [ 11 ]. Briefly, samples of pepper pods were collected at 3 different sampling points: (1) on the day of ripe fruits harvest (SP I); (2) during the drying process (1 month after harvest, SP II); and (3) during the smoking process (SP III).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported that pepper pods from different varieties of Capsicum are highly susceptible to the proliferation of spoilage genera fungi such as Botrytis , Cladosporium , Harzia , Rhizopus , and Phytophthora , including yet mycotoxigenic species such as Aspergillus flavus , A. niger , A. ochraceus , Penicillium expansum , and P. thomii [ 9 , 11 , 12 ]. Overall, pepper pods from field and post-harvest are predominantly contaminated with fungal strains of Alternaria / Fusarium and Aspergillus / Penicillium , respectively [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%